2020
DOI: 10.4049/jimmunol.2000319
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Uric Acid Is an Intrinsic Negative Regulator of Monocyte Activation in Monosodium Urate Crystal–Induced Tissue Inflammation

Abstract: Although monosodium urate (MSU) crystals are known to trigger inflammation, published data on soluble uric acid (sUA) in this context are discrepant. We hypothesized that diverse sUA preparation methods account for this discrepancy and that an animal model with clinically relevant levels of asymptomatic hyperuricemia and gouty arthritis can ultimately clarify this issue. To test this, we cultured human monocytes with different sUA preparation solutions and found that solubilizing uric acid (UA) by prewarming c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 77 publications
4
47
0
1
Order By: Relevance
“…First, studies have shown uric acid to be an important antioxidant [ 25 ] and poor outcomes in patients with hypouricemia might be related to reduced defense against oxidative stress. Second, uric acid was found to act as an endogenous modulator of innate immunity, and it is tempting to speculate that low levels of serum uric acid may therefore exacerbate the cytokine storm observed during COVID-19 [ 26 , 27 ]. Third, recent evidence demonstrated that acute and severe hypouricemia induced in healthy individuals causes endothelial dysfunction, reduces blood pressure, decreases myeloperoxidase activity and increases lipid peroxidation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, studies have shown uric acid to be an important antioxidant [ 25 ] and poor outcomes in patients with hypouricemia might be related to reduced defense against oxidative stress. Second, uric acid was found to act as an endogenous modulator of innate immunity, and it is tempting to speculate that low levels of serum uric acid may therefore exacerbate the cytokine storm observed during COVID-19 [ 26 , 27 ]. Third, recent evidence demonstrated that acute and severe hypouricemia induced in healthy individuals causes endothelial dysfunction, reduces blood pressure, decreases myeloperoxidase activity and increases lipid peroxidation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major symptom of a gout flare is the MSU crystal-induced sterile inflammation with UA controversially being an intrinsic inhibitor of MSU crystal-induced tissue inflammation [49] and a direct promoter in inflammation in vivo [50]. Hyperuricemia could induce an activated status of inflammation [51] or autoinflammation [52].…”
Section: Distinct Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…Moreover, asymptomatic hyperuricemia patients usually display less potency of inflammation with a lower number of NKG2D + (activating receptors of simulation of cytotoxicity) NK cells [63]. It could be speculated that under hyperuricemia condition the UA paradox interrelationship of the contradictory dual effects of inflammation [49,50] results from SUA "neutralizing" the inflammation produced oxygen species to protect tissue damages. It has also been discovered that some lipids from diet or alcohol consumption could directly trigger gout flares by activation of NALP-3 inflammasome through binding to toll-like receptors [64] or alteration of glucose and apolipoprotein metabolism [65], respectively.…”
Section: Distinct Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…The major symptom of a gout attack or flare is the MSU crystal-induced sterile inflammation with UA controversially being an intrinsic inhibitor of MSU crystal-induced tissue inflammation [49] and a direct promoter in inflammation in vivo [50]. Hyperuricemia could induce an activated status of inflammation [51] or autoinflammation [52].…”
Section: Deferent Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…Moreover, asymptomatic hyperuricemia patients usually display less potency of inflammation with a lower number of NKG2D + (activating receptors of simulation of cytotoxicity) NK cells [63]. It could be speculated that under hyperuricemia condition the UA paradox inter-relationship of the contradictory dual-effects to inflammation [49,50] is resulted from SUA to "neutralize" the inflammation produced oxygen species to protect tissue damages. It has also been discovered that some lipids from diet or alcohol consumption could directly trigger gout flare by activation of NALP-3 inflammasome through binding to toll-like receptors [64] or alteration of glucose and apolipoprotein metabolism [65], respectively.…”
Section: Deferent Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%